PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Nova Ayu Maulita; Nurma Gupita Dewi (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
ABSTRACTThe goal of this research was to exarmine the impact of leverage, liquidity, profitability and firm size on quality of earnings. This study obtained 54 samples of food and beverage company entities listed on the IDX for the 2019-2021 period using a purposive sampling method. Methods of data collection using documentation. The data analysis technique uses multiple linear regression analysis with SPSS version 19. The results of this study indicate that partially leverage has a significant negative effect on earnings quality. Liquidity and profitability partially have no significant negative effect on earnings quality. And the size of the firm does not affect the quality of earnings.Keywords : leverage; liquidity; profitability; firm size; earnings quality